ASSESSMENT OF TOURISM DEVELOPMENT IN THE RUSSIAN FEDERATION - Platonova, Natalya; Pogrebova, Elena (Revista Inclusiones, 2020)
The socio-economic system of Russia has entered a new stage of its development, whose external manifestation consists in the growth of economic recovery rates, stabilization of inflation indicators, the revival of investment activity, and changes in consumer sentiment towards domestic producers. In such conditions, tourism can be defined as a new effective tool for socio-economic development of the Russian Federation. Tourism makes a significant contribution to ensuring sustainable socioeconomic development and social stability. This industry is important for the development of small businesses and microenterprises, as well as creating jobs and contributing also to self-employment of the population. The tourism industry is developing faster than the global average growth rate, encouraging the development of related economic sectors. Today, tourism accounts for 3.4% of the country’s gross domestic product, affecting 53 related industries. The creation of one job in the tourism sector entails the creation of up to five jobs in related industries.